Knowledge of the risks, hygiene habits and perceived health issues associated with pesticide mixing and application among smallholder farmers - Shade J. Akinsete; Oluwaseun T. Adejumo; Mumuni Adejumo; Haruna Musa Moda; Stella Ibifunmilola (PLoS ONE, 2026)
Smallholder farmers’ exposure to pesticide can be minimized by their hygiene behaviour during pesticide application. The aim of this study was to determine knowledge of the risks, hygiene habits and perceived health issues associated with pesticide mixing and application among smallholder farmers in Nigeria. A cross-sectional study was conducted on 162 smallholder farmers from Ibarapa North Local Government Area, using a validated structured questionnaire through a two-stage sampling method. Data were analyzed using descriptive statistics and chi-square test at p = 0.05. Farmers’ mean age was 42.4 ± 12.3 years, 85.0% were male while 32.9% had tertiary education. Most (95.1%) farmers acknowledged that pesticides affect human health and 63.1% read, understood and followed pesticides label. Notably, only 4.9% acknowledged that banned or restricted pesticides cannot be used. Respondents identified pesticide exposure routes as inhalation (74.7%), dermal (15.4%), oral (1.9%) and eye contact (0.6%). Mean knowledge score was 7.9 ± 2.7 and 54.3% had poor knowledge of pesticide risk. Majority of farmers had direct skin contact with pesticide (83.3%) while 21.3% wore pesticide contaminated farm cloth home. Respondents’ use of personal protective equipment (PPE) during pesticide mixing and application were: goggles (10.1%), coverall (29.0%), head cover (22.9%) and gloves (41.8%). Additionally, unsafe disposal of empty pesticide containers on farm was common among the farmers (42.6%). Mean hygiene habit score was 5.8 ± 1.9 and 85.2% had unsafe hygiene habit. Respondents’ (90.9%) who had poor knowledge of pesticide risk was significantly (p = 0.025) higher among those who had unsafe hygiene habit during pesticide mixing and application. Reported symptoms by farmers included: dizziness > itchy eye > headache = skin irritation > nausea = coughing, during or after pesticide mixing and application. Farmers’ knowledge about pesticide risk and safe hygiene habit was poor. Farmers’ health may be at risk, hence appropriate hygiene habit and use of PPE should be strictly adhered to during pesticide mixing and application.